2012
DOI: 10.1016/j.ejps.2012.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cell membrane thiols and reduction-triggered disassembly on transfection activity of bioreducible polyplexes

Abstract: Bioreducible polyplexes are promising vectors for delivery of nucleic acids due to low toxicity and favorable transfection activity. The often improved transfection is usually explained by enhanced intracellular reductive disassembly of the polyplexes. This study evaluated the effect of enhanced reductive disassembly on transfection activity of plasmid DNA and antisense oligonucleotide (AON) polyplexes based on a series of bioreducible poly(amido amine)s (PAA). We found that the presence of disulfide bonds in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Intracellular degradation of the reducible polycations not only contributes to efficient disassembly of the polyplexes, but also to better spatial selectivity of release of the nucleic acids in the cytoplasm and to decreased cytotoxicity. Furthermore, the interactions between the reducible polyplexes and cell surface thiols are also playing an important role in improving cellular uptake of reducible polyplexes [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Intracellular degradation of the reducible polycations not only contributes to efficient disassembly of the polyplexes, but also to better spatial selectivity of release of the nucleic acids in the cytoplasm and to decreased cytotoxicity. Furthermore, the interactions between the reducible polyplexes and cell surface thiols are also playing an important role in improving cellular uptake of reducible polyplexes [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we speculate that this behavior is specific for bioreducible lipoplexes. Nonetheless, it is worth noting that the outcome of the reduction process mediated by EPTs is likely to be determined by numerous factors including the site of disulfide introduction within the gene transfer vector [9,47], the type of non-viral vehicle used [13,49], the dose of complexes delivered to cells [23] as well as the concentration and the site where the reducing species reside [6][7][8][9].…”
Section: Dna Release From Bioreducible Lipoplexes: the Yin Effect Of mentioning
confidence: 99%
“…Li et al 14 reported that 0.75 M NaCl in HBS was indispensable for pDNA release. Incubation with 20 mM GSH resulted in the dissociation of the complexes (CAR/CHL-CBA) and a release of pDNA at N/P ratios from 1/6 to 1/48.…”
Section: Reduction Sensitivity Of the Gua-ss-paasmentioning
confidence: 99%
“…However, PEGylated SS-PAAs also showed lower transfection efficiency than SS-PAAs. Salmaso et al 17 and Li et al 14 investigated the effect of cell membrane thiols and reduction-triggered disassembly on the transfection activity of bioreducible polyplexes, which revealed that the plasma membrane protein thiols played a key role in the observed enhancement of DNA transfection.…”
Section: Introductionmentioning
confidence: 99%